2009
DOI: 10.3109/08860220903100671
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Residual Kidney Function after Twelve Years' Hemodialysis

Abstract: Residual kidney function (RKF) contributes significantly to solute clearance and fluid removal for dialysis patients, and the presence of RKF is associated with less morbidity and better long-term outcome. Most studies demonstrate that peritoneal dialysis preserves RKF better than hemodialysis (HD). Herein, we report a 55-year-old man with end stage renal failure who had been on chronic HD for 12 years. His RKF is preserved with very slow decline during the past years. Without specific intervention, delicate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Avoidance of aggressive water removal, even without water removal, is beneficial for the preservation of RRF in dialysis patients. 10,11 Hyodo and Koutoku 12 compared the RRF in HD patients without water removal with that in patients with water removal, and the results showed that the urine volume in those without water removal was significantly larger. However, the present study indicated that preservation of RRF with limited water removal in HD patients must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of aggressive water removal, even without water removal, is beneficial for the preservation of RRF in dialysis patients. 10,11 Hyodo and Koutoku 12 compared the RRF in HD patients without water removal with that in patients with water removal, and the results showed that the urine volume in those without water removal was significantly larger. However, the present study indicated that preservation of RRF with limited water removal in HD patients must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%